ISSUES OF IMPROVING THE EFFECTIVENESS OF PROTECTING THE RIGHTS OF MINOR VICTIMS IN UZBEKISTAN (World Bulletin of Management and Law, 2025)
Juvenile victims require comprehensive legal protection frameworks to safeguard their rights and ensure their well-being in society. Despite existing regulatory mechanisms, gaps in legal protection continue to affect the effectiveness of safeguarding minors' rights within the criminal justice system. The article discusses the rights of juvenile victims, the regulatory legal acts concerning their legal protection, and the significance of the amendments made for the comprehensive improvement of minors' lives in our society. It also covers statistics on juvenile victims and emphasizes the inevitability of punishment for any violence against minors. The study employed retrospective and comparative methods to analyze the effectiveness of protecting the rights of minor victims. The research determined that consolidating the status of minor victims in a separate article within the Criminal Procedure Code is necessary for enhanced protection. Statistical data on juvenile victims demonstrated the urgency of legislative improvements, while the study of recent amendments showed their positive impact on comprehensive protection mechanisms. These regulatory improvements represent critical steps toward establishing a more effective system for protecting juvenile victims in society